The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1992
DOI: 10.1017/s0899367x00002683
|View full text |Cite
|
Sign up to set email alerts
|

Protest Bidders in Contingent Valuation

Abstract: Protest bids are often excluded during analysis of contingent valuation method data. It is suggested that this procedure might introduce significant bias. Protest bids are often registered by respondents who may actually place ahigher-orlower-than-average value on the commodity in question but refuse to pay on the basis of ethical or other reasons. Exclusion of protest bids may therefore bias willingness to pay (WTP) results, but the direction of bias is indeterminate a priori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(108 citation statements)
references
References 24 publications
3
97
0
4
Order By: Relevance
“…Those who answered "I agree" to this question were assumed to have a lexicographic preference (Stevens et al 1991;Spash and Hanley 1995) toward maintaining the current level of multifunctionality. On the other hand, they were assumed to protest against the CVM question (Halstead et al 1992) if they answered "I cannot answer until more concrete measures are shown," "I am opposed to the tax increase," "The use of tax revenue should be improved without increasing tax," "There are no nonagricultural measures to supplement the weakening of multifunctionality," or "Other reasons" to the item that questioned respondents who answered "no" to both the CVM questions about the reason for their answers. Respondents with a lexicographic preference and respondents who were opposed to the CVM question were eliminated from the following CVM analysis, along with those whose responses were incomplete.…”
Section: Econometric Modelingmentioning
confidence: 99%
“…Those who answered "I agree" to this question were assumed to have a lexicographic preference (Stevens et al 1991;Spash and Hanley 1995) toward maintaining the current level of multifunctionality. On the other hand, they were assumed to protest against the CVM question (Halstead et al 1992) if they answered "I cannot answer until more concrete measures are shown," "I am opposed to the tax increase," "The use of tax revenue should be improved without increasing tax," "There are no nonagricultural measures to supplement the weakening of multifunctionality," or "Other reasons" to the item that questioned respondents who answered "no" to both the CVM questions about the reason for their answers. Respondents with a lexicographic preference and respondents who were opposed to the CVM question were eliminated from the following CVM analysis, along with those whose responses were incomplete.…”
Section: Econometric Modelingmentioning
confidence: 99%
“…Do these negative responses reflect true zero values or do they reflect an objection to the valuation process itself? Including protesters, respondents who object to the valuation process, can bias estimates of WTP (Halstead et al 1992). Recognizing the importance of this problem, many authors adjust for protest responses by identifying them and truncating them from the sample (for example see Boyle et al 1993;Jorgensen et al 1999;Whittington et al 1992).…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
“…Protest bids occur whenever individuals who oppose or do not approve of the survey fail to respond, give invalid but positive bids (outliers), or place a zero value on a good that they actually value [45]. The latter category seems to describe the behavior of respondents classified as protest bids in our study.…”
Section: Responses To Value-eliciting Questionsmentioning
confidence: 84%